The unknown church-historical project of hieromonk German (Weinberg), future bishop of Alma-Ata - Alexander Kravetsky (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2021)
The article studies the scholarly heritage of Bishop German (Weinberg), who prepared a reference book with information on more than one hundred services to Russian saints which were compiled in the 18th — early 20th centuries. Until recently, nothing was known about the scholarly work of Bishop German, who died in a forced labour camp in 1942. Some time ago, a manuscript of his dissertation entitled Services to Russian saints created during the Synodal period of Russian church life and supplementary materials for this work were found in the Russian National Library. These materials are currently being prepared for publication. The value of Bishop German’s study is due to the fact that when compiling the history of services he used the archives of the Synod and those of the Censorship Department. In conformity with Russian laws, the approval of the liturgical text for publication was accompanied by a long bureaucratic correspondence. This correspondence is an invaluable source for reconstructing the history of compilation and editing of church services. This work made it possible to establish the names of the authors and editors of a large number of church services. The work of Bishop German should be viewed in the general context of the re-emerging interest in Russian saints which marked the reign of Nicholas II. Since nothing was known about the existence of this study, at least three attempts to design such a reference book were made in the 20th century. Boris Sove collected materials for a similar work in Helsinki. In 1951, Feodosiy Spasskiy published the history of services to Russian saints in Paris. In 1964–1965, Archpriest Rostislav Lozinskiy presented a dissertation on this topic in Moscow Theological Academy. However, none of these authors ever turned to archival materials, therefore Bishop German’s study remains unsurpassed and relevant. At present, an edition of Bishop German’s materials is being prepared; it will be supplemented with data on those editorial corrections which were made in services to Russian saints in the post-revolutionary period.